Principles of chemistry - Munowitz, M. (Michael) (W.W. Norton, 2000)
Read a few pages, and you'll see what all the excitement is about. Intended primarily for college freshmen, this exceptionally lucid, carefully paced, elegantly designed, well-illustrated volume will appeal to curious readers of any age who want to know more about the innermost workings of the "central science." In the words of another advance reviewer, the Munowitz book "reveals the beauty of chemistry in an unusual, graceful, narrative style. Compared with standard textbooks, it is poetic.